2020
DOI: 10.1007/s10758-020-09463-5
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Digital Media Self-Efficacy and Its Importance for Higher Education Institutions: Development and Validation of a Survey Instrument

Abstract: Although digital media are in general very common, their role in academic settings and their relevance for academic achievement are not satisfactorily explored. A research gap that is particularly apparent during the corona crisis in 2020 when university processes in many countries are suddenly almost completely digitalised. Research suggests a link between students’ diversity, in particular, their socio-economic background, academic self-efficacy expectations, study-related attitudes, and academic achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 45 publications
2
48
0
4
Order By: Relevance
“…In this context, the remark of Hodges (2008) becomes pertinent that the role of self-efficacy in online environments is only in its infancy that needs more studies. To this note, subsequent researchers studied the role of self-efficacy in online education, and the spotlight of these studies mostly was on the technology factor of self-efficacy in online learning, like computer self-efficacy (Pellas, 2014), Internet self-efficacy (Lin et al , 2013; Kuo et al , 2014), digital media self-efficacy (Pumptow and Brahm, 2020), learning management system (LMS), self-efficacy (Prior et al , 2016; Martin et al , 2010) and ICT self-efficacy (Cusso-Calabuig et al , 2018; So et al , 2012). Few studies focused on the role of self-efficacy, task value (Joo et al , 2013) and academic self-efficacy factors (Jan, 2015; Cho and Shen, 2013; Yokoyama, 2019), and few others focused on the general self-efficacy (Gebara, 2010) in online education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the remark of Hodges (2008) becomes pertinent that the role of self-efficacy in online environments is only in its infancy that needs more studies. To this note, subsequent researchers studied the role of self-efficacy in online education, and the spotlight of these studies mostly was on the technology factor of self-efficacy in online learning, like computer self-efficacy (Pellas, 2014), Internet self-efficacy (Lin et al , 2013; Kuo et al , 2014), digital media self-efficacy (Pumptow and Brahm, 2020), learning management system (LMS), self-efficacy (Prior et al , 2016; Martin et al , 2010) and ICT self-efficacy (Cusso-Calabuig et al , 2018; So et al , 2012). Few studies focused on the role of self-efficacy, task value (Joo et al , 2013) and academic self-efficacy factors (Jan, 2015; Cho and Shen, 2013; Yokoyama, 2019), and few others focused on the general self-efficacy (Gebara, 2010) in online education.…”
Section: Discussionmentioning
confidence: 99%
“…Purpose of the study Thus, self-efficacy, the intrinsic self-belief, has a big role in academic activities, including online education (Pumptow and Brahm, 2020). Bandura (1997) himself found that because of the swift progress of technological tools, the pedagogical use of technology may require special and ever-evolving types of teacher self-efficacy.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Teo (2014) and Hatlevik (2017) demonstrated a positive relationship between self-efficacy about using digital tools and the use of ICT for teaching purposes. But studies like Pumptow & Brahm (2020), Hatlevik & Hatlevik (2018), or Ertmer & Ottenbreit-Leftwich (2010) found several other internal factors make this integration successful for the teachers like technological knowledge, pedagogical knowledge, content knowledge, that jointly composed teachers' ICT selfefficacy belief. These are all teacher related human factors affecting ICT use.…”
Section: Self-efficacy An Internal Factor For Ict Integrationmentioning
confidence: 99%
“…The importance of the role of parents in the development of learning at home (Albintary et al, 2018). Child development is influenced by parenting self-efficacy (Pumptow & Brahm, 2020) parenting self-efficacy helps children to develop themselves and obtain a joint evaluation (Opoku et al, 2020). The importance of self-efficacy can help children to improve life skills and good attitudes.…”
Section: Problem Of Researchmentioning
confidence: 99%